Murine Sertoli cells promote the development of tolerogenic dendritic cells: a pivotal role of galectin‐1. Issue 3 (4th May 2016) - Gao, Jianxin; Wang, Xujie; Wang, Yunchuan; Han, Fu; Cai, Weixia; Zhao, Bin; Li, Yan; Han, Shichao; Wu, Xue; Hu, Dahai
Summary: Sertoli cells (SCs) possess inherent immunosuppressive properties and are major contributors to the immunoprivileged status of mammalian testis. SCs have been reported to inhibit the activation of B cells, T cells and natural killer cells but not dendritic cells (DCs). Herein, we present evidence that co‐culture with SCs results in a persistent state of DC immaturity characterized by down‐regulation of the surface molecules I‐A/E, CD80, CD83, CD86, CCR7 and CD11c, as well as reduced production of pro‐inflammatory cytokines. SC‐conditioned DCs (SC‐DCs) displayed low immunogenicity and enhanced immunoregulatory functions, including the inhibition of T‐cell proliferation and the promotion of Foxp3 + regulatory T‐cell development. Mechanistically, the activation of p38, extracellular signal‐regulated kinase 1/2, and signal transducer and activator of transcription 3 was suppressed in SC‐DCs. More importantly, we demonstrate that galectin‐1 secreted by SCs plays a pivotal role in the differentiation of functionally tolerogenic SC‐DCs. These findings further support the role of SCs in maintaining the immunoprivileged environment of the testis and provide a novel approach to derive tolerogenic DCs, which may lead to alternative therapeutic strategies for the treatment of immunopathogenic diseases.